Dinamika Sosial Ekonomi Petani Jagung Kuning di Desa Tontorita Kecamatan Biringbulu Kabupaten Gowa 1985-2005 - Sukiman Sukiman (Universitas Islam Negeri Alauddin Makassar, 2015)
The aim of this study to discover the social and economic life of yellow corn farmers in the Tonrorita village, Biringbulu District, Gowa Regency, by uncovering the background of the society which develop yellow corn plants. Then to describe the development of yellow corn plants in Tonrorita Village. Moreover, to analyze the impact of yellow corn the changing of social and economic in the Tonrorita Village society, Biringbulu Districts, Gowa.This research is a historical description using historical methods that include heuristic, critic, interpretation, and historiography or writing a historical narrative. Then the results showed that the yellow maize crop development in the Tonrorita Village, District of Biringbulu began in 1985. That is the start of the public to switch from hazelnut cultivation to the yellow corn cultivation. The role of government couldn’t be separated from the success of the yellow maize crop, namely the provision of capital, formation of farmer groups and agricultural extension.From the results of this study concluded that increasing yellow maize cultivation in the Tonrorita Village, Biringbulu District, Gowa Regency has a very broad impact to the farmers. Farmer economic level was increasingly prosperous, as well as the fulfillment of social needs of farmers.